Interpreting that function as y=x2+2x+1, the graph of this function would be a parabola that opens upward. It would be equivalent to y=(x+1)2. Its vertex would be at (-1,0) and this vertex would be the parabola's only zero.
Chat with our AI personalities
4X + 2x = 1. Where x = 0.166666666666666666666666666666666666666 recurring.
One way would be to graph the two equations: the parabola y = x² + 4x + 3, and the straight line y = 2x + 6. The two points where the straight line intersects the parabola are the solutions. The 2 solution points are (1,8) and (-3,0)
X2 + 2X - 14 = 6X2 + 2X - 8 = 0what two products of - 8 = 2 ?(X +4)(X - 2)=========X = - 4X = 2
x2-2x-15 = (x+3)(x-5) when factored
It keeps the same shape and size, but the whole thing rises four units on the paper, as if by magic.